“ANGGUN NAN TONGGA”, “MANDI ANGIN”, AND “WAYANG PADANG” AS INDONESIAN POSTMODERN THEATRICAL PRACTICES - -, Syafril (E-Journal of Cultural Studies, 2013)
This study explored “Anggun Nan Tongga”, “MandiAngin”, and “Wayang Padang” which were produced by Bumi Theatre Padang Group and were regarded as the real Indonesian theatrical practice. The Indonesian postmodern theatrical practices, which are regarded as the real ones, are different from the previous Indonesian modern theatrical practices which are considered the pseudo and false ones, although they were accepted as the real ones. This study was intended to identify the form, the influential factors, and the meaning of the Indonesian postmodern practices produced by the Bumi Theatre Padang Group in the three theatres mentioned above.   The results of the study showed ANT, MA, and WP were in the forms of relative art and contextual aesthetic concept. They were decentrally and democratically created. The existence of the viewers was used as the subject. The management of the culture-oriented production activity, group and society.The professionalization of the group and members in the cultural quality and humanity. The influential factors included the ideology of power, hegemony, the failure of becoming the Indonesian theatre, the attempt made to develop Indonesian theatre, the reformation which tended to be postmodern in Indonesia, the change in global postmodern culture. These could be defined as identity, cultural defense, social plurality, the real democracy, the critical and creative productivity, and religiosity.
Keywords: “Anggun Nan Tongga”, “MandiAngin”, “Wayang Padang”, Indonesian postmodern theatrical practices.